MANAJEMEN PROGRAM TAHFIDZ AL QURAN DALAM PENGEMBANGAN KARAKTER DISIPLIN SISWA DI MI PSM GEDORO NGAWI - Asroriah, Fatimah (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2022)
Discipline character of students can grow well if it is based on the individual's willingness to make good habits and through a long and sustainable process that involves the role of the family, educational institutions and social environment. This study aims to determine: 1) The pattern of student discipline character formation through routine tahfidz Al-quran at MI PSM Gedoro. 2). The process of forming students' disciplined charactersthrough the routine of Tahfidz Al Quran at MI PSM Gedoro 3). The impact of routine tahfidz Al Quran on the formation of student discipline character at MI PSM Gedoro. This research is a type of descriptive qualitative research. The analysis technique includes interactive analysis, sources and research data, namely people, events and documents. While the data collection techniques using interviews, observation and documentation. The results of the study explain that: 1). The routine activities of tahfidz Al Quran at MI PSM Gedoro use the Wahdah method. Sima'i, Muraja'ah, and Takrir. 2). Discipline character of students at MI PSM Gedoro is emphasized on: Student attendance at school on time, active in learning activities, obedience to school rules, having a good attitude, carrying out worship according to the provisions. dress neatly according to regulations. 3). The routine activities of Tahfidz al-Quran have a very significant impact on the process of forming student discipline character at MI PSM Gedoro.